2013
DOI: 10.1074/jbc.m113.470567
|View full text |Cite
|
Sign up to set email alerts
|

Role of Central Metabolism in the Osmoadaptation of the Halophilic Bacterium Chromohalobacter salexigens

Abstract: Background:Chromohalobacter salexigens synthesizes and accumulates ectoines. Results: High ratio of the anaplerotic and catabolic fluxes involved in ectoines synthesis supports high biosynthetic fluxes at high salinity and leads to metabolite overflow at low salinity. Conclusion: Evolution optimized the metabolism of C. salexigens to support high production of ectoines. Significance: Metabolic adaptations in a compatible solute-accumulating halophile are described for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(112 citation statements)
references
References 61 publications
7
100
1
4
Order By: Relevance
“…It has been shown recently that the glucose catabolism in C . salexigens and other bacteria of the Halomonadaceae proceeds entirely via the ED-pathway [26, 42]. A possible explanation from these differences can be attributed to the specificity of the 6-phosphofructokinase present in H .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown recently that the glucose catabolism in C . salexigens and other bacteria of the Halomonadaceae proceeds entirely via the ED-pathway [26, 42]. A possible explanation from these differences can be attributed to the specificity of the 6-phosphofructokinase present in H .…”
Section: Resultsmentioning
confidence: 99%
“…elongata and other halophilic bacteria that allow them to cope with salt concentrations well above 1.7 M NaCl (10%). In a recent paper, Pastor and coworkers analyzed the metabolism of the halophilic bacterium Chromohalobacter salexigens [26], which has a similar salt tolerance to H . elongata and synthesizes ectoine as its major compatible solute.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular accumulation of these solutes enables cells to maintain osmotic balance and avoid irreversible dehydration. These compounds may reach high concentrations without interference with cellular processes (Roessler and Müller, 2001;Pastor et al, 2013). Compatible solutes can be divided into several structural groups: sugars (trehalose, surcose), polyols (glicerol, sorbitol, mannitol, α-glucosyl-glycerol, mannosyl-glycerol, mannosyl-glyceramide), N-acetylated diamino acids (like N-acetylglutaminylglutamine amide), betaines (such as glycine betaine and derivatives), amino acids (proline, glutamate, glutamine, alanine, ectoine and hydroxyectoine) and derivatives (Yancey, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicated that CO may be lethal to fish if used at excessive concentrations or if regulations about time of aneshesia specific for a single fish species are not followed (Sladky et al, 2001).This compound also causes various toxic effects in human colon cancer cell lines in the in vitro conditions and in insects, therefore it has been used as an insecticide (US EPA, 2004;Boyer et al, 2009).The potential harmful effects of CO on nontarget aquatic animals such as invertebrates was also reported. For example, a reduction growth and bleaching of corals was observed after repeated field application of the oil (Pastor et al, 2013).…”
Section: Introductionmentioning
confidence: 99%